Paker Digital Application in Making Palliative Nursing Care - Rindy Antika; Karolin Adhisty; Khoirul Latifin (Jurnal Berita Ilmu Keperawatan, 2023)
Digital documentation as legal ethics in reporting nursing care is a way to save and evaluate the actions taken by nurses. Digital documentation has several advantages rather than manual documentation, including increased communication between nurses, and medical workers as well as the effectiveness of time in making nursing care documentation better. This study aims to create Android-based digital documentation which can be used as a guide in providing palliative nursing care for cancer patients with a focus on physical and social problems. The research design that used in this research was research and development (R&D) with a quantitative approach and ADDIE development model. The trial of this application was conducted on 15 nursing students with a purposive sampling technique. The Blackbox and application eligibility test got an 83 score which showed that this application is categorized as excellent, acceptable, and suitable for use. Documentation is an important part of making nursing care which must be learned and mastered by nurses through lectures. Studying documentation from assessment to evaluation can improve the professional ability of prospective nurses in providing real implementation to patients. This application can be a useful tool for nurses as a medium for learning nursing care documentation.